2004
DOI: 10.1038/sj.emboj.7600360
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2 decreases Mash1 stability by increasing Id1 expression

Abstract: In neural development, bone morphogenetic proteins (BMPs) restrict neuronal differentiation, thereby promoting the maintenance of progenitor cells or even inducing astrocytogenesis. We report that exposure of neuroendocrine lung carcinoma cells to BMP-2 leads to a rapid decline in steady-state levels of Mash1 protein and some neuron-specific markers. BMP-2 induces a post-transcriptional decrease in Mash1 levels through enhanced degradation. We demonstrate that Mash1 protein stability is tightly regulated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 54 publications
9
119
0
1
Order By: Relevance
“…As development proceeds, this signal may also act in migrating GABAergic interneurons since PI3K has been reported to regulate tangential migration of neocortical interneurons (44). Proneural bHLH proteins are key determinants of neuronal fate in the developing telencephalon (13,15), and several studies have shown how these proteins are regulated posttranscriptionally by extrinsic cues (20)(21)(22)(23)(24). Our data now suggest that the PDK1-Akt pathway mediates regulation of Mash1 by extrinsic cues.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…As development proceeds, this signal may also act in migrating GABAergic interneurons since PI3K has been reported to regulate tangential migration of neocortical interneurons (44). Proneural bHLH proteins are key determinants of neuronal fate in the developing telencephalon (13,15), and several studies have shown how these proteins are regulated posttranscriptionally by extrinsic cues (20)(21)(22)(23)(24). Our data now suggest that the PDK1-Akt pathway mediates regulation of Mash1 by extrinsic cues.…”
Section: Discussionsupporting
confidence: 62%
“…Ngns and Mash1 are expressed in complementary patterns in the dorsal and ventral parts of the telencephalon, contributing to the generation of glutamatergic and GABAergic neurons, respectively (17,18). Although some transcriptional/posttranscriptional regulations on these transcription factors have been revealed, it largely remains unclear how they are regulated by neurogenic extrinsic cues during CNS development (7,(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Surprisingly, Smads, the main transcriptional effectors of BMPs, do not seem to play a major role in regulating gene expression in BMP-treated quiescent NS cells, since the consensus Smad-binding motif is not significantly overrepresented in enhancers active in quiescent NS cells (data not shown). Genes of the inhibitor of differentiation (Id) family are major targets of BMP signaling in many tissues, including the embryonic nervous system (Nakashima et al 2001;Samanta and Kessler 2004;Vinals et al 2004). The four family members, and particularly Id1 and Id4, are highly up-regulated in quiescent NS cells and may therefore contribute significantly to the quiescence-inducing activity of BMP.…”
Section: Bmp Signaling and Quiescencementioning
confidence: 99%
“…Vinals et al (2004) demonstrated that overexpression of E47 can sequester Id proteins, thus inhibiting Id function. However, overexpression of E47 did not have any obvious influence on progenitor cell fates.…”
Section: Loss Of Id Functionmentioning
confidence: 99%